(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
The aim of this study was to determine the genetic diversity and relationships among twenty newly developed genotypes of Cyamopsis tetragonoloba using Randomly Amplified Polymorphic DNA (RAPD) molecular technique. Data obtained from application of ten molecular markers were subjected to the procedure of clusters analysis. Random Amplified Polymorphic DNA (RAPD) molecular markers indicated the presence of a wide genetic diversity among the studied twenty genotypes of guar. The constructed dendrogram, based on Jaccard’s similarity coefficients, differentiated the genotypes into seven main clusters. The closest genotypes were genotypes Gm34 and L53 with (98 % similarity), while the most diverse ones were genotype L14 and genotype Gm16 with 29% genetic similarity. It was concluded that use of RAPD markers can be used for efficient estimation of genetic diversity in guar. Hence, the current investigation can contribute to enhancement of molecular breeding approach for the development of improved guar genotypes.